2022
DOI: 10.1016/j.jpubeco.2021.104587
|View full text |Cite
|
Sign up to set email alerts
|

Tax evasion and tax avoidance

Abstract: Exploiting rich administrative data and salient policy variation, we study the substitution between illegal tax evasion and legal tax avoidance. By increasing its enforcement effort, the Norwegian government pushed many wealthy individuals to disclose assets previously hidden abroad. We find that the taxes paid by these individuals rise 30% at the time of disclosure and that the rise is sustained over time. After stopping to evade, taxpayers do not start avoiding more. Our results suggest that cracking down on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
4

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 32 publications
1
20
0
4
Order By: Relevance
“…The higher the value of the leverage ratio, the higher the amount of funding from third party debt used by the company and the higher the interest costs arising from the debt. The results of this study are in line with research conducted showed that leverage had no effect on tax avoidance (Alstadsaeter et al, 2022;Damayanti & Wulandari, 2021).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The higher the value of the leverage ratio, the higher the amount of funding from third party debt used by the company and the higher the interest costs arising from the debt. The results of this study are in line with research conducted showed that leverage had no effect on tax avoidance (Alstadsaeter et al, 2022;Damayanti & Wulandari, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…Taxes are one of the biggest contributors to a country's income (Alstadsaeter et al, 2022;Uemura, 2022). This can be seen in the growth of tax revenue in 2019 of 1,545.3 Trillion Rupiah's, compared to nontax state revenue in the same year, which was only 405 Trillion Rupiah (Damayanti & Wulandari, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to the existence of a centralized third-party platform, this can easily lead to fraudulent behaviors such as data and signature tampering. On the other hand, in the process of financial investment, there is a problem of paying taxes [4]. To evade taxes, the financial investment advisor signs a "yin-yang contract" with the client.…”
Section: Introductionmentioning
confidence: 99%
“…Some elements of the creative accounting of business entities are reflected in tax evasion. Tax evasion is a negative phenomenon in Slovakia and throughout the world (Terzic & Berger, 2020;Li et al, 2021;Ermasova, Haumann & Burke, 2021;Alstadsaeter et al, 2022). It is not entirely possible to eliminate tax evasion, but it is possible to reduce the incidence of tax evasion (Ngah, Ismail & Abd Hamid, 2021;Hungerman, 2022;Rashid et al, 2022;Hola, Zidkova, & Arltova, 2022;Mu, Fentaw, & Zhang, 2022;Slemrod & Velayudhan 2022).…”
Section: Introductionmentioning
confidence: 99%